Implementasi Standar Pedoman Nasional Terhadap Tujuan Pendidikan Jasmani - Ariestika, Elsa; widiyanto, widiyanto; Nanda, Fitri Agung (Pusat Studi Ilmu Keolahragaan, Fakultas Ilmu Keolahragaan, Universitas Negeri Padang, 2021)
Abstract Quality education is highly dependent on the existence of quality teachers, namely teachers who are professional, prosperous, and dignified, so that later the movement experience students get in Physical Education is an important contributor to increasing the participation rate in physical activity and sports which is also an important contributor to student welfare and health. This study aims to determine the National Standards and Guidelines for Physical Education. The method used in this study is to use literature study. The data were collected using bibliographical studies from previous studies, and also a collection of articles from scientific journals. The results of this literature study research indicate that the main goal of physical education is to understand how students perceive students to be taught, increase perceptions to improve physical awareness, guide students to have an active lifestyle. Through the NASPE standards, physical education should help students become active in the learning process. Through physical education it can form children, namely attitudes or values, intelligence, physical, and skills (psychomotor), so that students will be mature and independent, which can later be used in everyday life.